Waqf unit trust as an alternate model to realize waqf sustainability - Khaliq, Ahmad; Hussin, Nazimah; Mohammad, Mohammad Tahir Sabit (Università degli Studi di Torino, 2019)
With poverty and unemployment is still the paramount concern across the globe, a study on Waqf and capital market integrations is certainly a timely call for sustainable socio-economic development. The aim of this paper is to revisit the literature on the issue of illiquidity of Waqf assets and eradicate the dependency on government provision. To ensure the sustainability of Waqf institutions, financing apparatus primarily designed for Waqf assets are explored. The study proposes a viable integration of Waqf and capital market apparatus of Unit Trust investments based on the Shariah-compliant standards ratified by the Security Commission of Malaysia (SCM) guidelines. The study opts for thematic analysis method of the existing literature on Waqf financing. The finding indicates that there is a need for a novel apparatus such Waqf unit trust instrument through cash Waqf and share Waqf to realizes greater Waqf funds accumulation, investment, and distribution. It is highly advocated that the income of investment be optimally utilized for socio-economic projects. This study realizes as one of the pioneer endeavors to pool Waqf fund via unit trust model as its sources and exhibit management undertakings of the model.